Improving the clinical efficacy of drugs by liposomes against resistant bacteria (mdr bacteria) – an in vitro study - M. JAINAMBOO; S.T. GOPUKUMAR; P.K. PRASEETHA (International Journal of Pharma and Bio Sciences, 2017)
Control of drug-resistant bacteria involved in severe infections acquired in hospital (ICUs) patients are extremely challenging, due to increased levels of antimicrobial resistance presented by microorganism against most antimicrobial agents routinely used. Liposomes are spherical vesicles, with particle sizes ranging from 30 nm to several micrometers, consisting of one or more lipid bilayers surrounding aqueous spaces. Our designed study aimed at knowing the importance of encapsulating antimicrobial drugs into multilamellar liposomes to overcome microbial resistance, when administered as a liposomal formulation by localizing antibiotic to the periplasmic space, allowing it to exert its bactericidal activity. Drug resistant bacteria such as ESBL positive (E. coli, Klebsiella pneumonia), Acinetobacter baumanii, Staph aureus and Methicillin resistant Staph aureus were isolated from around 1750 clinical specimens. The bactericidal activity of drug was tested in vitro by MIC and Disc diffusion. Different antibiotics (Amikacin, Ciprofloxacin, Cloxacillin and Vancomycin) loaded with high efficiency on to these multilamellar vesicles were prepared by the simple thin film hydration method using egg yolk. In vitro antimicrobial activities were determined in comparison to free drug by Inhibition zone using agar well diffusion and were compared with ATCC strains. Antimicrobial activity of polyethylene glycol coated liposomal antibiotics against clinical strains and ATCC strain was compared to free drugs. Further, for Liposomal characterization UV, FTIR, AFM, TEM were used and encapsulation efficiency was also included in this study. Microbiological experiments in vitro was shown to be able to inhibit to a different extent the growth of clinical strain and ATCC strain. Inhibition zone for antibiotic diffusion was as high as 30-40 mm were observed, against clinical isolates used in this study. In comparison, neither the free drug nor liposomes showed any activity against the same bacteria. Moreover, it was noticed that the therapeutic potential of 4 drugs improves by encapsulation in PEG.